Morphogenetic and tillering dynamics in Tanzania grass fertilized and non-fertilized with nitrogen according to season - Roma, Cláudio Fabrício da Cruz; Cecato, Ulysses; Soares Filho, Cecilio Viega [UNESP]; Santos, Geraldo Tadeu dos; Ribeiro, Ossival Lolato; Iwamoto, Bruno Shigueo (Sociedade Brasileira de Zootecnia, 2012)
The objectives of this study were to evaluate morphogenetic characteristics and tillering dynamics in Tanzania grass fertilized and non-fertilized with nitrogen, under intermittent grazing, in the spring and the summer. The main plots were composed of four nitrogen rates (0, 100, 200 and 300 kg/ha) and the subplots were growth seasons: spring (October, November and December) and summer (January, February and March). The experimental design was of randomized block with plots subdivided by time (seasons of the year) and four replications. Urea was used as nitrogen supply and was divided into two applications: one in the spring and another in the summer. The experimental units fertilized with N rates of 200 and 300 kg/ha showed six cycles of pasture, with an average of 27 days of pasture interval, while the treatments with no fertilization and 100 kg/ha of N showed only four and five cycles of pasture, respectively. Leaf elongation rate (LER) and the leaf appearance rate (LAR) increased linearly with increasing of N rates. The greatest population density occurred in summer with the higher nitrogen rates. The treatment without N fertilization showed the lowest growth of tiller population, while the other treatments exhibited growth rates above 50% when compared with non-fertilized samples. Nitrogen rates significantly affect the leaf appearance rate and the leaf elongation rate, as well as the number of live leaves in plants of Tanzania grass in both spring and summer.
Keywords: intermittent grazing; leaf appearance rate; leaf elongation rate; Panicum maximum; senescence rate